2017
DOI: 10.18203/2394-6040.ijcmph20171756
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on dietary patterns among pregnant women attending antenatal care check-up in Narayani hospital, Nepal

Abstract: Background: Pregnancy is the period from conception to birth during which there is the requirements of diet that provide the required essential nutrients to keep the mother healthy and allow the fetus to grow and develop in favorable conditions. The objective of the study was to identify the knowledge on dietary pattern among pregnant women attending ANC checkup in Narayani sub-regional hospital. Methods: The study was of descriptive, cross sectional type. The random sampling technique was applied. The study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Nutrition education is the foundation for any program intended for nutritional improvement [ 1 ]. The knowledge about proper nutrition and balanced diet during pregnancy is considered important for the well-being of both mother and fetus [ 2 ]. During pregnancy nutritional problems can impact on both mother and fetus, thus special attention is needed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition education is the foundation for any program intended for nutritional improvement [ 1 ]. The knowledge about proper nutrition and balanced diet during pregnancy is considered important for the well-being of both mother and fetus [ 2 ]. During pregnancy nutritional problems can impact on both mother and fetus, thus special attention is needed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 This result differs with findings of a Nepalese study that although every expectant mother had little knowledge on nutrition, still there is lack of adequate knowledge on dietary patterns during expectancy and some wrong perceptions following diet consumption during gravidity was found. 22 The result also differs with another study that found out that knowledge regarding sources of carbohydrates/proteins, iron, zinc, vitamin A and iodine was low in Yemen. 23…”
Section: Foods Mothers Advised To Takementioning
confidence: 58%
“…While there are no published studies addressing women's perceptions of the importance of REs during labor to compare our results with, another report showed that wrong knowledge about certain food groups during pregnancy affected women's perception of their importance and subsequently affected their intake. This again reflects the importance of not only knowledge but also knowledge content ( Shah et al, 2017 ). The inconvenience level associated with REs in our cohort was low; this is probably related to the procedure being simple.…”
Section: Discussionmentioning
confidence: 85%